Deep Learning Convolutional Neural Networks for Content Based Image Retrieval (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Content Based Image Retrieval (CBIR) has received an excellent deal of interest within the researchcommunity. A CBIR system operates on the visible features at low-level of a user's input image that makes it troublesome for the users to devise the input and additionally doesn't offer adequate retrieval results. In CBIR system, the study of the useful representation of features and appropriate similarity metrics is extremely necessary for improving the performance of retrieval task. Semantic gap has been the main issue which occurs between image pixels at low-level and semantics at high-level interpreted by humans. Among varied methods, machine learning (ML) has been explored as a feasible way to reduce the semantic gap. Inspired by the current success of deep learning methods for computer vision applications, in this paper, we aim to confront an advance deep learning method, known as Convolutional Neural Network (CNN), for studying feature representations and similarity measures. In this paper, we explored the applications of CNNs towards solving classification andretrieval problems. For retrieval of similar images, we agreed on using transfer learning to apply the deep architecture to our problem. Extracting the last-but-one fully connected layer from the retraining of proposed CNN model served as the feature vectors for each image, computing Euclidean distances between these feature vectors and that of our query image to return the closest matches in the dataset